A utilização do setor elétrico como instrumento de implementação de políticas públicas e os reflexos para a sociedade brasileira (1995-2004) - Alves, Job de Figueiredo Silvério (2006)
This work analyzes the use of Brazilian electrical sector by the State as an implementation tool of public policies in the period that goes from 1995 to 2004 when different institutional regulation models were instituted in the country. These models varied from the defense of the free market virtues to the recovering of rooms to the state presence. This work intends to highlight the intrinsic problems to the conformation of the State strategies as a conductor or coordinator of the social-economic development, as well as, the negative reflexes brought to society, from the reading of the electric energy public services evolution in Brazil and the particularities of the policy cycle. The State actions exploring the potential of the Brazilian electrical sector in the implementation of the public policies are questioned here based on the means they are worth, from the submission of the technical principles to the political-socialideological variables, the results they will reach and the lack of transparency of its basic principles. The established relations concerning the use and the production of electric energy considering its economic and social character are good issues to the representation of the multiple rooms for the political power practice through a perspective that breaks up the opposition between the State and society enhancing their complementarity.